The Effect of Assessment Techniques on EFL Learners' achievement in TOEFL Test - شھد حاتم كاظم (College of Education for Women, 2019)
While many educators are highly focused on state test, it is important to consider that over the course of a year, instructors can build in many opportunities to assess how learners are learning. Therefore, assessment techniques are considered a good method to get benefit for both instructors and learners in the process of teaching and learning. The sample consists of 27 learners who participated in TOEFL training course in the Development and Continuous Education Centre. Validity and reliability were verified. To fulfill the aims and verify the hypothesis which reads as follows" It is hypothesized that the TOEFL learners' scores will not be increased after TOEFL course training." T-test for two dependent samples is used to obtain the results. The analysis of the results shows that the learners' score in posttest and TOEFL ITP test is better than pretest. In the light of the results, several conclusions, recommendations and suggestions for future study have been made.